Strategi Marketing Politik Calon Independen Dalam Kontestasi Pilkada Serentak Tahun 2017 Di Kabupaten Buton Selatan - Ansar Suherman; Mansur . (JURNAL ILMU SOSIAL, 2017)
This research aims to know the marketing strategy of a political candidate from the independent online election Districts are simultaneously carried out in 2017. This research took South Buton regency location in Southeast Sulawesi Province and made of candidate La Ode Agus Mbaeda and La Ode Agus (AA) as a subject in the study because it comes from an independent or non-line political party. In identifying a political marketing strategy undertaken by the prospective spouses AA, researchers used a model of political marketing from Smith and Hirst, who use the three phases namely: segmentation, targeting, and positioning politics. The research approach applied in the research is descriptive qualitative approach. Through this approach, the problem can be a breakfast buffet clearly and details of segmentation, targeting, and Positioning Politics that will have an impact on the determination of strategies and tactics to win team consolidation. The results of this study found that the process of segmentation has been done by the team to win even though the process is not done thorough and complete. The team winning only focuses on one segment of the course, i.e. ethnic culture/social segments with the neglect of other segments which should be entered in part a process of segmentation. On the targeting of the winner, the team approach as a strategy of ethnic-based which is considered able to obtain support vote by utilizing custom personalities as the main target. It is a phenomenon in rural communities that the community would be so listen to what was said by the indigenous character. Primordialism approach in the context of rural communities in Indonesia can still be used as a decoy to get support. On the final stage, due to segmentation and targeting only focuses on one segment alone IE social culture/ethnicity, then the team winning more political positioning accentuates regional son issues because it is believed to be still strongly influences the perception community voters.